Workplace Hostility - Manuela R. Collis; Clémentine Van Effenterre (Institute of Labor Economics (IZA), 2025)
We investigate how much individuals value a workplace that doesn't tolerate hostility, and how these preferences affect sorting in the labor market. We conduct a choice experiment involving 2,048 participants recruited from recent graduates and alumni from a large public university. Our results show that individuals are willing to forgo a significant portion of their earnings—between 12 and 36 percent of their wage—to avoid hostile work environments, valuations substantially exceeding those for remote work (7 percent). Women exhibit a stronger aversion to exclusionary workplaces and environments with sexual harassment. Combining survey evidence, experimental variations of workplace environments, and individual labor market outcomes, we show that both disutility from workplace hostility and perceptions of risk contribute to gender gaps in early-career choices and in pay. To quantify equilibrium implications, we develop a model of compensating differentials calibrated to our experimental estimates. Using counterfactual exercises, we find that gender differences in risk of workplace hostility drive both the remote pay penalty and office workers' rents.
Keywords: J16; J24; J31; 330; workplace hostility; compensating differentials; gender